2009
DOI: 10.1016/j.nbd.2009.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of soluble TNF signaling in a mouse model of Alzheimer's disease prevents pre-plaque amyloid-associated neuropathology

Abstract: Microglial activation and overproduction of inflammatory mediators in the central nervous system (CNS) have been implicated in Alzheimer's disease (AD). Elevated levels of the pro-inflammatory cytokine Tumor Necrosis Factor (TNF) have been reported in serum and post-mortem brains of patients with AD, but its role in progression of AD is unclear. Using novel engineered dominant negative TNF inhibitors (DN-TNFs) selective for soluble TNF (solTNF), we investigated whether blocking TNF signaling with chronic infus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
184
2
5

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 236 publications
(205 citation statements)
references
References 80 publications
14
184
2
5
Order By: Relevance
“…Thus, the chronic increase in pro-inflammatory cytokines in the AD brain [134,135] could induce sustained inflammatory-toxicity, causing neuronal dysfunction and ultimately the deterioration observed in AD progression. Furthermore, as noted above, cytokines can also influence AD-related pathology, including Ab and tau [67,79,136,137]. Moreover, indoleamine 2, 3-dioxygenase, which is activated by cytokines, may be an additional candidate mechanism of cytokineinduced AD pathology and could lead to increased levels of the neurotoxic factor, quinolinic acid [138], and promote tau hyperphosphorylation [139].…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Thus, the chronic increase in pro-inflammatory cytokines in the AD brain [134,135] could induce sustained inflammatory-toxicity, causing neuronal dysfunction and ultimately the deterioration observed in AD progression. Furthermore, as noted above, cytokines can also influence AD-related pathology, including Ab and tau [67,79,136,137]. Moreover, indoleamine 2, 3-dioxygenase, which is activated by cytokines, may be an additional candidate mechanism of cytokineinduced AD pathology and could lead to increased levels of the neurotoxic factor, quinolinic acid [138], and promote tau hyperphosphorylation [139].…”
Section: Discussionmentioning
confidence: 94%
“…In animal models of AD, increased TNF-a is a key element in inflammatory cascade and increases the Ab and tau pathology [77]. Moreover, short-term anti-TNF-a treatment improves cognition in AD patients [78], probably by relieving the Ab pathology [79]. However, neuroprotective roles of TNF-a have also been reported, as long-term and non-specific inhibition of TNF-a signaling worsens the AD-related pathology in the brains of AD transgenic mice [80].…”
Section: Tnfamentioning
confidence: 99%
“…TNF-α has also been shown to participate in the Aβ-induced inhibition of LTP, which is most likely dependent on p38MAPK [49] . The inhibition of TNF-α signaling has been shown to attenuate AD-like pathology and www.nature.com/aps Zhang LL et al Acta Pharmacologica Sinica npg cognitive impairments in transgenic mouse models as well as in AD patients [50,51] , whereas the upregulation of TNF-α has been shown to exacerbate AD pathology. Indeed, TNF-α levels have been found to be elevated within the cerebrospinal fluid (CSF) of AD patients by as much as 25-fold [52] .…”
Section: Discussionmentioning
confidence: 99%
“…[11][12][13][14] Our laboratory previously demonstrated a pre-pathological up-regulation of TNF-␣ and correlating enhancement of F4/ 80-positive microglia/macrophage numbers in the 6-monthold triple-transgenic AD (3xTg-AD) mouse model that exhibits an age-related development of amyloid and tau pathological features and deficits in synaptic plasticity, including hippocampal long-term potentiation (LTP), reminiscent of human AD. 15,16 McAlpine et al 17 recently reported that viral vector-mediated expression of truncated TNF receptor in lipopolysaccharide-infused 3xTg-AD mice suppresses AD-related amyloid pathological features in the short-term. In further support of a potential contributory role of TNF-␣ to AD pathogenesis, long-term TNF-␣ overexpression via viral vector-based gene transfer leads to enhanced inflammation and marked neuronal cell death in this mouse model of AD.…”
mentioning
confidence: 99%